ANALYSIS OF STAFF INVOLVEMENT IN THE WORK IN THE DEPARTMENT HEALTH DISTRICT SLEMAN (Case study in Sleman District Health Office) - One, Suyati; Lastari, SE., MM., Siwi; Nawarcono, SE., MM, Winanto (Management, 2010)
Performance is influenced by individual characteristics (ability and skill, personality, perception, attitude, experience, gender, age, race, traits, and learning capacity) and the work environment (organizational structure, job design, policies, rules, awards, and sanctions and resources). Performance is the performance results of operations of both quantity and quality employees in an organization. Assessment of performance through self assessment (self assessment) is the most common approach to measuring and understanding individual differences. Of the 40 respondents, 34 respondents were in the score 50-74 entering the medium category, while others are located at 6 respondents score 75-100 are included in the high category. And nothing at all that is in the score 25-49 of respondents means that does not exist at all employees who are in the low category. From the above data it can be concluded that the Employees´ Involvement in Sleman District Health Office Who´s because 34 respondents from 40 respondents as a whole is in the medium category, while another 6 respondents who are in the high category and nothing at all that is in the low category. Upshot: Employee Involvement Sleman District Health Office if viewed from the employees´ loyalty Medium. Based on the results of research conducted on the Involvement of Employees Working in Sleman District Health Office, it can be concluded that: 1. The amount of employee involvement in completing the work in Sleman District Health Office of average height when seen from the analysis that there were 33 respondents from 40 respondents or 82.5%. 2. Sleman District Health Office personnel almost all have been involved in completing a job in Sleman District Health Office. Keywords : staff involvement, work in the department health